2022
DOI: 10.1097/mpg.0000000000003404
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hepatitis in Pediatric Coronavirus Disease 2019

Abstract: Hepatic involvement in coronavirus disease 2019 is typically characterized as mild hepatitis with preserved synthetic function in children. Severe hepatitis is a rare complication of COVID-19 infection that has not been extensively described in the pediatric population. We report a case series of four previously healthy children who presented with significant hepatitis as the primary manifestation of COVID-19 infection. Two of these patients met criteria for acute liver failure. None of the patients had respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…Sgouropoulou et al reported a 5-year-old pediatric patient who presented with transient acute hepatitis after SARS-CoV-2 infection (17). Antala et al described a 6-month-old infant who presented with acute liver failure as a subacute presentation of COVID-19 disease (7). On admission he tested positive for SARS-CoV-2 PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sgouropoulou et al reported a 5-year-old pediatric patient who presented with transient acute hepatitis after SARS-CoV-2 infection (17). Antala et al described a 6-month-old infant who presented with acute liver failure as a subacute presentation of COVID-19 disease (7). On admission he tested positive for SARS-CoV-2 PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In children and adolescents, COVID-19 is generally mild (3); however, multisystem inflammatory syndrome (MIS-C) is a serious possible consequence (4). in this age group, liver involvement was described with acute COVID-19 and with MIS-C. Mostly, transaminases were elevated, without hepatic synthetic dysfunction, though acute liver failure was also reported (5)(6)(7). Children who developed elevated alanine aminotransferase were at risk of a more severe disease course, including longer hospitalization and stay in the intensive care unit (ICU).…”
mentioning
confidence: 99%
“…A liver biopsy could not be performed, as the patient was unstable and hypo-coagulable, however, an exhaustive workup for other causes of ALF was negative. Considering recent case reports showing COVID-19 infection as a direct cause of acute hepatitis in children [ 5 ], our case report emphasizes the importance of further research into the possible association between COVID-19 and isolated ALF.…”
Section: Discussionmentioning
confidence: 65%
“…A usual clinical course of COVID-19 infection involves upper respiratory infection, fever, chills, and anosmia, followed by viral pneumonia, severe acute respiratory distress syndrome, and multiorgan failure [ 3 ]. Recently, there have been few case reports of COVID-19 infection in children presenting as severe acute hepatitis [ 5 ]. Our report describes a case of an adult woman presenting with severe ALF as her only presenting sign and symptom of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to rarely impaired pulmonary function, respiratory system symptoms persist in approximately 30% of patients at 3 months after SARS‐CoV‐2 infection 9 . Compared with adults, severe hepatitis could be a critical concern for a long‐term follow‐up in children with COVID‐19 10 . Consistently, Brodin et al.…”
Section: The Long‐term Impaired Organ Function In Children With Sars‐...mentioning
confidence: 78%